Comparative study of reactivity of (-)-R-carvone, (-)-R-linalool and (-)-(1S,4S)-camphor derivatives: Synthesis of new heterocycles - Rouani, Mohamed; Rahmouni, Bouchra; Chammache, Malika; El-Mebtoul, Aziz; Ilidrissi, Abdelkader (European Journal of Chemistry, 2014)
Reactivity comparison by 1,3-dipolar cycloaddition of the three dipolarophiles (-)-R-Carvone (I), (-)-R-Linalool (II) and derivative of (-)-(1S,4S)-camphor (III) has been studied. By reactions of p-chlorophenylnitrile oxide, new heterocycles are obtained by stereospecific reactions for cyclic Terpenoids I and III (regardless of the length of the side chain). However the aliphatic dipolarophile II gives two diastereoisomers. Terpenoids (-)-R-Carvone I (-)-R-Linalool II and (-)-(1S,4S)-Camphor 1 are isolated respectively from Moroccan species Mentha viridis (L.), Lavandula officinalis (L.) and Artemisia herba halba (Asso). The new heterocycles obtained were identified by combination of chromatographic and spectroscopic methods.